Additive Destabilization of Porous Magnesium Borohydride Framework with Core‐Shell Structure. Issue 44 (27th September 2021) - Dun, Chaochao; Jeong, Sohee; Liu, Yi‐Sheng; Leick, Noemi; Mattox, Tracy M.; Guo, Jinghua; Lee, Joo‐Won; Gennett, Thomas; Stavila, Vitalie; Urban, Jeffrey J.
Abstract: Design of interfaces with thermodynamic and kinetic specificity is of great importance for hydrogen storage from both an applied and fundamental perspective. Here, in order to destabilize the metal hydride and protect the dehydrogenated products from oxidizing, a unique core‐shell structure of porous Mg(BH4 )2 ‐based framework with a thin layer (no more than 5 nm) of MgCl2 additives on the surface, has been proposed and synthesized via a wet‐chemical method. The local structure and electronic state of the present complex system are systematically investigated to understand the correlation between the distribution of additives and dehydrogenation property of Mg(BH4 )2 . A significant improvement is achieved for hydrogen desorption with chlorides: initial hydrogen release from MgCl2 decorated γ‐phase Mg(BH4 )2 particles commences at 100 °C and reaches a maximum of 9.4 wt% at 385 °C. Besides the decreased decomposition temperature, an activation barrier of about 76.4 kJ mol −1 lower than that of Mg(BH4 )2 without MgCl2 is obtained. Moreover, MgCl2 decoration can also prevent the whole decomposed system (both Mg‐ and B‐ elements) from oxidizing, which is a necessary condition to reversibility. Abstract : A unique core‐shell structure of porous γ‐phase Mg(BH4 )2 with a thin layer of MgCl2 additives on the surface, has been proposed and synthesized via a wet‐chemical method. The initial hydrogen release from MgCl2 decorated Mg(BH4 )2 particles commences at 100 °C and reaches a maximum of 9.4 wt% at 385 °C.